A STUDY ON THE IMPACTS OF DIGITAL STORYTELLING ON EFL LEARNERS’ SELF-EFFICACY AND ATTITUDES TOWARD EDUCATION TECHNOLOGIES - Balaman, Sevda (International Online Journal of Education and Teaching, 2020)
This study aimed to investigate whether a digital storytelling (DS)-integrated pedagogy was effective for developing students’ self-efficacy and attitudes toward educational technology. 43 English-as-a-foreign-language (EFL) English-major students from the School of Foreign Languages (SFL) at Cumhuriyet University (CU) participated into this study. There were two groups in the study, namely experimental and control groups. The experimental group was exposed to DS-integrated instruction while no intervention was given to the control group. Control group students followed their regular course requirements. Before and after the experiment, both groups were tested by using a survey aiming to determine learners’ self-efficacy beliefs for and attitudes toward the use of technology in education. The quantitative data indicated the exposure to the DS impacted the experimental groups students’ efficacy and attitudes toward educational technology in the positive direction. However, the control group students’ scores did not exhibit a noticeable change. The qualitative data also documented that students heightened their self-efficacy and had a positive stance for the use of technology in their learning as result of participation into this experiment. The resulting information can be helpful for those who are willing to create a teaching environment that meets the needs and expectations of 21st century students.